Facilitating Dialogues in an Online Classroom: Insights from an EFL Classroom - Cassandra, Nina Wanda; Hamied, Fuad Abdul; Muslim, Ahmad Bukhori; Isti Saleha Gandana (Indonesian Research Journal in Education |IRJE|, 2024)
Research on classroom discussions and dialogues is well-established, however, studies on how classroom dialogue is facilitated in online classrooms remain underexplored. This qualitative case study addresses this gap by examining the experiences of an EFL teacher educator and her 16 students during a twelve-week enacting dialogic pedagogy mediated by Microsoft Teams (MT). Utilizing thematic analysis from thirteen video recordings, four discussion forums, three series of teacher interviews, student feedback, and researchers' observations, the study revealed that the classroom dialogue was facilitated in MT by structuring the online environment, enhancing synchronous video conferencing through ‘meet now,’ extending dialogue through chat-based learning in ‘channel,’ and enriching interaction with multimodal cues. The study suggests that while digital technologies can enhance dialogic activities, it is crucial for teachers and students to enhance and maintain their dialogic stance and digital competence in online classrooms.